2021
DOI: 10.3390/geriatrics6040112
|View full text |Cite
|
Sign up to set email alerts
|

How Do Geriatric Scores Predict 1-Year Mortality in Elderly Patients with Suspected Pneumonia?

Abstract: Background: Pneumonia has an impact on long-term mortality in elderly patients. The risk factors associated with poor long-term outcomes are understated. We aimed to assess the ability of scores that evaluate patients’ comorbidities (cumulative illness rating scale—geriatric, CIRS-G), malnutrition (mini nutritional assessment, MNA) and functionality (functional independence measure, FIM) to predict 1-year mortality in a cohort of older patients having a suspicion of pneumonia. Methods: Our prospective study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In older patients with non-metastatic cancer, studies are showing that among the 8 comorbidity indexes, only CIRS-G predicts 1-year mortality [34]. In another study, comorbidity burden as assessed by CIRS-G, and malnutrition were shown to be important predictors of 1-year mortality for the long-term prognosis of older patients hospitalized for pneumonia [35]. In a study conducted on older patients with protein-energy malnutrition, it was shown that the CIRS-G score was higher, and cognitive de cit and dependence on activities of daily living were higher [36].…”
Section: Discussionmentioning
confidence: 98%
“…In older patients with non-metastatic cancer, studies are showing that among the 8 comorbidity indexes, only CIRS-G predicts 1-year mortality [34]. In another study, comorbidity burden as assessed by CIRS-G, and malnutrition were shown to be important predictors of 1-year mortality for the long-term prognosis of older patients hospitalized for pneumonia [35]. In a study conducted on older patients with protein-energy malnutrition, it was shown that the CIRS-G score was higher, and cognitive de cit and dependence on activities of daily living were higher [36].…”
Section: Discussionmentioning
confidence: 98%